2020
DOI: 10.1186/s12913-020-05388-y
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a sentinel surveillance network for sexually transmissible infections and blood borne viruses in Aboriginal primary care services across Australia: the ATLAS project

Abstract: Background: Sexually transmissible infection (STI) and blood-borne virus (BBV) diagnoses data are a core component of the Australian National Notifiable Diseases Surveillance System (NNDSS). However, the NNDSS data alone is not enough to understand STI and BBV burden among priority population groups, like Aboriginal and Torres Strait Islander people, because it lacks testing, treatment and management data. Here, we describe the processes involved in establishing a STI and BBV sentinel surveillance network repr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…For example, the ATLAS indigenous primary care surveillance network aims to monitor the STi and BBv burden in Aboriginal and Torres Strait islander populations across Australia. 54 This network is partnered with the Aboriginal Community-Controlled Health Organisation sector and was designed to address the disparity in testing, treatment, and management of sexually transmissible infections and blood borne viruses, but as yet only a methods article has been published. 55 There are a number of other marginalised groups who are also important to consider in infectious disease surveillance.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the ATLAS indigenous primary care surveillance network aims to monitor the STi and BBv burden in Aboriginal and Torres Strait islander populations across Australia. 54 This network is partnered with the Aboriginal Community-Controlled Health Organisation sector and was designed to address the disparity in testing, treatment, and management of sexually transmissible infections and blood borne viruses, but as yet only a methods article has been published. 55 There are a number of other marginalised groups who are also important to consider in infectious disease surveillance.…”
Section: Discussionmentioning
confidence: 99%
“…Conducting analytical research, particularly across multiple states and territories or nationally, is a complex and costly endeavour. Further, although Aboriginal and Torres Strait Islander health research ethics processes ensure culturally safe and appropriate research practice, 26 conducting multisite ethics processes has been reported to affect timelines in trials 27 . Despite experimental research being classified as the gold standard, recent reviews have identified knowledge and methodological gaps in documenting Aboriginal and Torres Strait Islander health research impact 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Further, although Aboriginal and Torres Strait Islander health research ethics processes ensure culturally safe and appropriate research practice, 26 conducting multisite ethics processes has been reported to affect timelines in trials. 27 Despite experimental research being classified as the gold standard, recent reviews have identified knowledge and methodological gaps in documenting Aboriginal and Torres Strait Islander health research impact. 18 Furthermore, leading Aboriginal and Torres Strait Islander academics are calling for a reimagining of health systems and research through a health justice framework 28 to influence major changes to research priorities, including the research methods most highly valued.…”
Section: Discussionmentioning
confidence: 99%
“…28 This collaborative, mutually-beneficial model for Indigenous data collection has been replicated in studies such as the ATLAS project and its application to other Indigenous health contexts merits further consideration. 29 5. Finally, we need to move beyond traditional systematic reviews in Indigenous health research, in favour of approaches that are more inclusive of diverse and culturally appropriate forms of evidence.…”
Section: Refr Aming the Arg Umentmentioning
confidence: 99%
“…A key feature of the TTANGO project was a commitment to community engagement and ensuring that the research provided tangible benefits to participating services 28 . This collaborative, mutually‐beneficial model for Indigenous data collection has been replicated in studies such as the ATLAS project and its application to other Indigenous health contexts merits further consideration 29 …”
Section: Reframing the Argumentmentioning
confidence: 99%